KAJIAN PEMBERIAN LABU SIAM DAN AIR KELAPA MUDA TERHADAP PENURUNAN TEKANAN DARAH ( STUDI LITERATUR ) - Ainul Muthi'ah Alfaini; Endang Sutjiati; Rany Adelina (Politeknik Kesehatan Kemenkes Malang, 2023)
Background: Hypertension is one of the main causes of death in the world with mortality from systolic hypertension 2.5 times greater than mortality from diastolic hypertension. In Indonesia, the death rate induced by hypertension reached 427,218 in 2019. Providing interventions for hypertensive patients apart from medicines is also given some drinks or functional foods derived from local food ingredients. Siamese pumpkin and young coconut water can help contribute potassium which can help lower blood pressure in people with hypertension. Method: This type of research is literature review. with the research design using the method Traditional review. The type of data used is secondary data, totaling 10 original articles obtained from Google Scholar, ResearchGate and Google.com. The data is then compared and then analyzed descriptively. Results: there is an effect of giving chayote and young coconut water to reducing blood pressure in hypertensive patients with an average decrease of ± 30 mmHg for systolic blood pressure and ± 20 for diastolic blood pressure when giving chayote and an average decrease in blood pressure of ± 17 mmHg for blood pressure systolic blood pressure and ± 8 mmHg for diastolic blood pressure in young coconut water for 5 days. Conclusion: Giving chayote is more effective with a short time can give the same effect compared to coconut water.